Feasibility Study of Direct Measurement of Stellar Reaction 22Mg(α,p)25Al - Duy, Nguyen Ngoc; Khiem, Le Hong (Communications in Physics, 2011)
The stellar reaction 22Mg(α,p)25Al plays an important role for understanding the nucleosynthesis of stars. It has never investigated yet. We are planning to study this reaction in environment of X-rays burst with temperature T9 = 1÷3 GK using invert kinematics and thick target method. This paper shows a design for direct investigation of this reaction by simulation method. This design is necessary for experimental setup and for confirmation of the feasibility of the experiment.